An additional whole-exome sequencing study in 102 panel-undiagnosed patients: A retrospective study in a Chinese craniosynostosis cohort - Chen, Jieyi; Zhang, Ping; Peng, Meifang; Liu, Bo; Wang, Xiao; Du, Siyuan; Lu, Yao; Mu, Xiongzheng; Lu, Yulan; Wang, Sijia; Wu, Yingzhi (Frontiers in Genetics, 2022)
Craniosynostosis (CRS) is a disease with prematurely fused cranial sutures . In the last decade, the whole-exome sequencing (WES) was widely used in Caucasian populations. The WES largely contributed in genetic diagnosis and exploration on new genetic mechanisms of CRS. In this study, we enrolled 264 CRS patients in China. After a 17-gene-panel sequencing designed in the previous study, 139 patients were identified with pathogenic/likely pathogenic (P/LP) variants according to the ACMG guideline as positive genetic diagnosis. WES was then performed on 102 patients with negative genetic diagnosis by panel. Ten P/LP variants were additionally identified in ten patients, increasing the genetic diagnostic yield by 3.8% (10/264). The novel variants in ANKH, H1-4, EIF5A, SOX6, and ARID1B expanded the mutation spectra of CRS. Then we designed a compatible research pipeline (RP) for further exploration. The RP could detect all seven P/LP SNVs and InDels identified above, in addition to 15 candidate variants found in 13 patients with worthy of further study. In sum, the 17-gene panel and WES identified positive genetic diagnosis for 56.4% patients (149/264) in 16 genes. At last, in our estimation, the genetic testing strategy of “Panel-first” saves 24.3% of the cost compared with “WES only”, suggesting the “Panel-first” is an economical strategy.